2017
DOI: 10.1093/mnras/stx1416
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared emission in luminous quasars accompanied by nuclear outflows

Abstract: Combining large-area optical quasar surveys with the new far-infrared Herschel-ATLAS Data Release 1, we search for an observational signature associated with the minority of quasars possessing bright far-infrared (FIR) luminosities. We find that FIR-bright quasars show broad C iv emission line blueshifts in excess of that expected from the optical luminosity alone, indicating particularly powerful nuclear outflows. The quasars show no signs of having redder optical colours than the general ensemble of opticall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Within this model, quasars at z ≈ 2 which are actively driving winds are expected to show larger C iv blueshifts in their spectra. Maddox et al (2017) showed that the individual FIR detection rate of such quasars is higher than would be expected for their optical luminosities. More specifically, objects which are detected in the Herschel -ATLAS survey at 100-500 µm are disproportionately more likely to show large C iv blueshifts.…”
Section: Far-infrared Propertiesmentioning
confidence: 90%
“…Within this model, quasars at z ≈ 2 which are actively driving winds are expected to show larger C iv blueshifts in their spectra. Maddox et al (2017) showed that the individual FIR detection rate of such quasars is higher than would be expected for their optical luminosities. More specifically, objects which are detected in the Herschel -ATLAS survey at 100-500 µm are disproportionately more likely to show large C iv blueshifts.…”
Section: Far-infrared Propertiesmentioning
confidence: 90%
“…They also investigated the SFR as a function of C IV FWHM and the C IV line asymmetry; we have not made use of either of these two results as it is not clear that the FWHM of C IV has a clear relationship with black-hole mass (Coatman et al 2017) and the asymmetry parameter is different from the blueshifts investigated herein. However, Maddox et al (2017) perform a similar analysis to that of Harris et al (2016), measuring the C IV blueshifts (using the same definition adopted herein) of a sample of 1185 quasars at 1.6 < z < 4.8 with 2-σ detections at λ obs > 250µm (and a matched sample of undetected sources). Therefore we can compare our work to independent indicators of SFR as a function of both EW (Harris et al 2016) and blueshift (Maddox et al 2017); i.e., as a function of C IV distance.…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…However, Maddox et al (2017) perform a similar analysis to that of Harris et al (2016), measuring the C IV blueshifts (using the same definition adopted herein) of a sample of 1185 quasars at 1.6 < z < 4.8 with 2-σ detections at λ obs > 250µm (and a matched sample of undetected sources). Therefore we can compare our work to independent indicators of SFR as a function of both EW (Harris et al 2016) and blueshift (Maddox et al 2017); i.e., as a function of C IV distance.…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…Taken together with the results of Coatman et al (2019), where a correlation between the blueshift of [O iii] and the blueshift of the C iv emission line is seen, this implies that FIR-luminous quasars also exhibit stronger galaxy-scale outflows compared to their FIR-faint counterparts. The FIR bright quasars studied by Maddox et al (2017) are not reddened, but outflows and starburst activity are nevertheless being seen in this population. There is likely to be a considerable overlap between star formation, outflows, and the presence and clearing of dust in massive (active) galaxies, and obtaining observations at multiple wavelengths of the same objects in order to quantify these processes is the only way to move to a complete understanding of the interplay between SMBH accretion, outflows, and star formation, and their impact on galaxies at z > 2.…”
Section: Obscuring Dustmentioning
confidence: 92%
“…Thus, star formation in luminous quasar hosts can also persist after the dust has been cleared from the line of sight. Using a population of SDSS quasars, Maddox et al (2017) find that strong FIR emission (and therefore presumably star formation) is associated with strong nuclear outflows as traced by large C iv blueshifts. Taken together with the results of Coatman et al (2019), where a correlation between the blueshift of [O iii] and the blueshift of the C iv emission line is seen, this implies that FIR-luminous quasars also exhibit stronger galaxy-scale outflows compared to their FIR-faint counterparts.…”
Section: Obscuring Dustmentioning
confidence: 99%